Obstacles to School Progression in Rural Pakistan: An Analysis of Gender and Sibling Rivalry Using Field Survey Data - Sawada, Yasuyuki (2012)
This paper aims to identify the obstacles to school progression by using field surveys that were conducted in twenty-five Pakistani villages. The full-information maximum likelihood (FIML) estimation of the sequential schooling decision model reveals important dynamics of the gender difference in educational attainment, intrahousehold resource-allocation patterns, and transitory income and wealth effects. In the descriptive statistics as well as the econometric analyses, we find a high educational retention rate and observe that school progression rates between male and female students after secondary school are comparable. In particular, we find gender-specific and schooling-stage-specific birth-order effects on education. Our overall findings are consistent with the implications of optimal schooling behavior under binding credit constraints and the self-selection of education-friendly households. Finally, we find serious supply-side constraints which might arise from a village-level lack of demand for primary schools for girls.